Analysis of The Role of Internal Auditors in Preventing Financial Fraud in North Sumatra Regional Government Agencies - Irza Faridz Muhammad; Fitri Yani Panggabean; M. G. Gahluzi; Fathonah Azzahra; Ridho Al Khalik Nuari (CV. AFDIFAL MAJU BERKAH, 2025)
This research aims to analyze the role of internal auditors in preventing financial fraud in local government agencies in North Sumatra. APBD management is a process that includes budget preparation, implementation and accountability, with supervision as a key element to ensure transparency and accountability. Internal auditors play a strategic role in preventing and detecting financial fraud through independent assessments, periodic audits, and providing recommendations for improving financial management. Challenges faced include limited human resources, lack of understanding of audit standards, and weak organizational commitment to internal control. This research uses an exploratory qualitative approach, which allows for an in-depth understanding of the phenomena studied in a natural context. Data collection techniques were carried out through in-depth interviews, observation and documentation, with the North Sumatra Provincial Inspectorate auditor as the main subject. The selection of informants was carried out using the snowball technique, while data analysis involved reduction, data presentation, and inductive conclusion drawing. The research also utilizes secondary data, including performance reports of related institutions. The research results show that internal auditors have a significant role in identifying potential fraud, providing strategic recommendations, and increasing the efficiency and effectiveness of regional budget management. However, the realization of supervision performance is still below the target, as seen in the regional revenue optimization indicators and expenditure efficiency, which respectively reached 0% and 5.86% of the target. The main obstacle is the lack of follow-up on recommendations and the lack of optimal implementation of internal control. This research concludes that strengthening the capacity of internal auditors and increasing organizational commitment is very necessary to prevent financial fraud. With a more effective contribution, internal auditors can become the main pillar in supporting clean, transparent and accountable financial governance.